The iconographic role of azulejo frames. - de Carvalho, Rosário Salema (Word & Image)
This article documents the relations between the verbal and visual elements found on the frames used in Portuguese tile decorations. Frames are a constant presence in the history of Portuguese azulejos, from the late fifteenth century to the present day. Their role is to integrate the decorations within the surrounding architecture and other artforms (mainly gilt woodwork, easel painting, polychrome marble inlays, ceiling painting, sculptures, and textiles), as well as to structure systems with a varying degree of complexity, usually subordinated to the idea of artistic totality. Throughout the centuries, changes in taste have influenced the different kinds of frames, often regarded as a minor part of the decoration, and therefore more open to the introduction of new artistic styles. In the light of all this, it is clear that frames are not mere finishing elements, but an important means of designing architectural spaces and structuring tile decorations. Moreover, frames are often the vehicle for a visual and textual discourse that is part of the iconographic programme they enclose. As such, they play a decisive role in the history of Portuguese azulejos, highly relevant for today's international frame studies, and for the dialogue between images and words.